Construction of local gene network for revealing different liver function of rats fed deep-fried oil with or without resistant starch. (6th September 2016) - Wang, Zhiwei; Liao, Tianqi; Zhou, Zhongkai; Wang, Yuyang; Diao, Yongjia; Strappe, Padraig; Prenzler, Paul; Ayton, Jamie; Blanchard, Chris
Highlights: Up/down regulated genes and corresponding signaling pathways were used to construct LGN. Changes in genes induced by DO led to a larger probability of disease or infection. Signaling pathways of rats were almost the same between DO-containing diet and DO-RS diet. RS in DO-containing diet may mainly regulate the genes that related to DO damage. Abstract: To study the mechanism underlying the liver damage induced by deep-fried oil (DO) consumption and the beneficial effects from resistant starch (RS) supplement, differential gene expression and pathway network were analyzed based on RNA sequencing data from rats. The up/down regulated genes and corresponding signaling pathways were used to construct a novel local gene network (LGN). The topology of the network showed characteristics of small-world network, with some pathways demonstrating a high degree. Some changes in genes led to a larger probability occurrence of disease or infection with DO intake. More importantly, the main pathways were found to be almost the same between the two LGNs (30 pathways overlapped in total 48) with gene expression profile. This finding may indicate that RS supplement in DO-containing diet may mainly regulate the genes that related to DO damage, and RS in the diet may provide direct signals to the liver cells and modulate its effect through a network involving complex gene regulatory events. It is the first attempt to reveal the mechanism of the attenuation of liver dysfunction from RS supplement in the DO-containing diet using differential gene expression and pathway network.